Further clinical observations on the pulmonary effects of paraquat ingestion. - Higenbottam, T (1979)
Five patients are reported who developed evidence of acute lung damage after proved ingestion of paraquat. In two the lung changes resolved; in one an aspiration pneumonia occurred, which was successfully treated, while two developed fatal pulmonary oedema. These pulmonary complications after paraquat intoxication appear more common than the progressive pulmonary fibrosis previously described. It is suggested that acute pulmonary oedema is a response to large doses, usually of Gramoxone, that subclinical lung changes result from small doses, usually of Weedol, and that pulmonary fibrosis occurs after intermediate doses. Preliminary data on plasma paraquat concentrations suggest that these are of value in prognosis.